Characterization of the Liquid Fuel Produced from Catalytic Depolymerization of Polymeric Waste Using Batch Reactor - O. L. Rominiyi, M. A. Akintunde, E. I Bello, L. Lajide, O. M. Ikumapayi, O. T. Laseinde and B. A. Adaramola (Nature Environment and Pollution Technology)
The high rate of generation of plastic waste in the country and the fact that all other means of Municipal Plastic Waste (MPW) management techniques had failed leading to the requirement of efficient and alternative disposal technique-depolymerization. The technique involves heating the polymeric waste at an elevated temperature in an inert environment to produce condensable, non-condensable, hydrocarbon and biochar. The plastic waste was collected at the Ilokun dumpsite in Ado-Ekiti, southwest Nigeria. Each component of the waste samples was depolymerized in a batch reactor without the use of a catalyst and with the addition of 10 g of activated carbon (AC) and calcium oxide (CaO) as catalysts. The liquid fuels which were produced between the temperature range of 219 and 232 were blended with standard fuel. Fuel samples with conventional diesel and depolymerized plastic diesel were characterized based on ASTM standards. The results of the proximate and ultimate analysis indicated that percentage moisture content ranges from 0.00-0.18%, volatile matter ranges between 96.66-99.75% and percentage ash content ranges from 0.13-3.03%. Fixed carbon ranges from 0.004-0.31% while the Gross Heating Value (GHV) ranges from 42.66-45.87 MJ/kg. The CHONS analyzer indicated the percentage of carbon, hydrogen, oxygen, nitrogen, and sulfur content range 81.64-85.51%, 12-31-18.04%, 0.00-1.51%, 0.00-0.73%, and 0.10- 0.97% respectively. The results of the physiochemical properties of the samples show that the density, API gravity, Kinematic viscosity and Flash point vary from 0.76-0.83 (g/cm3), 38.98-54.68, 17-2.80 (cm2/s) and 50.0-70.0 (°C) respectively while Cloud point, Pour point, Fire point and Cetane index range from -20-15.0 (°C), -23-7 (°C), 61.0-79.0 (°C) and 38.50-47.0. The pH values of the liquid fuel samples vary from 6.60-3.30. The overall results of the characterization indicated the fuel samples have proximity to the properties of the conventional diesel following the ASTM D975, ASTM D4737, ASTM D1298, ASTM D445, ASTM D2709, and ASTM D482 standards. The depolymerized polymeric waste is sustainable, with a low cost of production. Hence a good substitute as an alternative fuel and means of wealth creation from waste.